2003
DOI: 10.1291/hypres.26.829
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac Hypertrophy by Hypertension and Exercise Training Exhibits Different Gene Expression of Enzymes in Energy Metabolism

Abstract: Hypertension-induced pathological cardiac hypertrophy (hypertensive heart) and exercise training-induced physiological cardiac hypertrophy (athletic heart) have differences in cardiac properties. We hypothesized that gene expression of energy metabolic enzymes differs between these two types of cardiac hypertrophy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
46
0
2

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(50 citation statements)
references
References 48 publications
1
46
0
2
Order By: Relevance
“…6 and Ref. 21, respectively) suggest the presence of other, yet-to-be identified, regulatory mechanism(s), which could compensate CD36 deficiency. One potential mechanism is activation of AMP-dependent protein kinase due to high circulating levels of leptin or angiotensin II in SHR (7,33,41,53).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…6 and Ref. 21, respectively) suggest the presence of other, yet-to-be identified, regulatory mechanism(s), which could compensate CD36 deficiency. One potential mechanism is activation of AMP-dependent protein kinase due to high circulating levels of leptin or angiotensin II in SHR (7,33,41,53).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, O'Donnell et al (35) presented evidence for a limitation in the transfer of cytosolic NADH to mitochondria when glycolytic flux is enhanced in normal hearts subjected to high workload. This limitation could become even more important in SHR hearts, which have an intrinsically elevated glycolytic activity associated with increased mRNA levels for phosphofructokinase and LDH (8,21,57 (25), and a reduced calcium transport in the sarcoplasmic reticulum (29), possibly through an inhibitory effect of cytosolic NADH on cardiac ryanodine receptors (61). Furthermore, it may favor free radical production by 1) activating cardiomyocyte NAD(P)H oxidase (31), an enzyme that is more highly expressed in SHR hearts (41); or 2) inducing the formation of the unstable ubisemiquinone radical (49).…”
Section: Discussionmentioning
confidence: 99%
“…It has been described that the energy production in cardiac hypertrophy in SHR showed a shift from the use of fatty acids toward the use of glucose (27). Iemitsu et al showed that the mRNA expression of key enzymes in the glycolytic metabolic pathway was markedly increased in the SHR hearts, indicating a decline of cardiac function (28). Diastolic dysfunction is to be expected in the SHR because of the increased wall thickness and fibrosis (29−31).…”
Section: Discussionmentioning
confidence: 99%
“…On the protein level, in cardiac muscle cells ATP and citrate concentrations are so high that the enzyme would be completely inhibited and therefore could not act as an allosteric regulated key enzyme (38). Interestingly, PFK mRNA was markedly higher in spontaneously hypertensive rats compared with control rats and remained unchanged by exercise training-induced cardiac hypertrophy compared with controls (19).…”
Section: Cardiac Gene Expression In Dtgrmentioning
confidence: 99%